The HIV/AIDS knowledge of grade 9 and 10 learners in Mabarhule High School in Mpumalanga - Sibuyi-Mathonsi, Queen (2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.